2003
DOI: 10.1128/mcb.23.21.7756-7766.2003
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor-Mediated Induction of ABCA1 in Macrophages

Abstract: ABCA1, the mutant molecule in Tangier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 49 publications
2
100
0
1
Order By: Relevance
“…Electrophoretic Mobility Shift Assays (EMSA)-EMSA were performed as described elsewhere (39). SREBP-1c expression vector was translated in vitro using TNT Coupled Reticulocyte Lysate Systems (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Electrophoretic Mobility Shift Assays (EMSA)-EMSA were performed as described elsewhere (39). SREBP-1c expression vector was translated in vitro using TNT Coupled Reticulocyte Lysate Systems (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR assays were performed as described in ref. 52. All samples were analyzed for ␤-actin, 36B4 expression, or 18S RNA in the same run as ABCA1, ABCG1, ABCA7, or MMP-9.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extracts were prepared in modified radioimmunoprecipitation assay buffer as described in ref. 52. Equal amounts of protein (15 g) were fractioned on a 4-15% gradient SDS͞polyacrylamide gel, then transferred to a nitrocellulose membrane, incubated with anti-ABCA1 and anti-␤-actin Abs, and processed with horseradish peroxidaseconjugated secondary Ab using SuperSignal West Pico Chemiluminescent substrate (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…Two RXR agonists, 9-cis RA and methoprene acid, increased promoter activity 2.7-and 1.5-fold. The RAR agonist, [14] who showed that the livers of TTNPB-fed mice did not show any changes in FAS mRNA expression. Untreated, RXRa-expressing cells showed a slight induction of promoter activity, whereas cells cotransfected with RARb, but not RAtreated, had an approximately 50% decreased FAS promoter activity (Fig.…”
Section: Effect Of Retinoids On the Fas Promotermentioning
confidence: 99%